PENGARUH PENGGUNAAN PODCAST RUANG 28 TERHADAP PEMENUHAN KEBUTUHAN INFORMASI SOSIAL POLITIK (SURVEI PADA PENGIKUT AKUN PODCAST RUANG 28) - Fransiscus Ferry Kurniawan (2024)
This research aims to explore the influence of using the Ruang 28 podcast on fulfilling socio-political needs. Podcasts have become a popular medium for conveying socio-political content to the public. This research focuses on the Ruang 28 podcast, which is known for its diverse and informative content regarding the latest socio-political issues in society. The research method used was an online survey of a number of respondents who were listeners of the Ruang 28 podcast. Uses and gratification theory, audiences have the right to freely choose which media they will use to fulfill their needs in various ways. To find out how effectively the use of podcasts (Variabel It was found that there is a fairly strong relationship between Variabels X and Y. The regression coefficient is positive. Therefore, it can be concluded that the higher the use of podcast space 28, the greater its influence on fulfilling the social and political information needs of its users. Through the coefficient of determination test, it was found that the use of room 28 podcasts had an influence of 36.8% and other factors were 63.2% outside the research. The research results show that the use of the Ruang 28 podcast significantly contributes to fulfilling the socio-political needs of respondents. This research makes an important contribution to understanding the role of podcasts in meeting socio-political needs. The implications of this research can be used by media and communication practitioners to expand the use of podcasts as an effective means of disseminating socio-political information and building communities that care about these issues. Keywords: podcast, meeting information needs, uses and gratification theory